2001
DOI: 10.1055/s-2001-12195
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Response to Surgical Stress in Schoolchildren

Abstract: Postoperative hormonal response among children of school age is characterised by increases in ACTH, cortisol and beta-endorphin one hour after surgery, and by high concentrations of beta-endorphin 24 hours after surgery. Cortisol is an index of surgical stress. Emergency surgery is associated with significant increases in ACTH and cortisol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…The study confirms the results reached in previous research in children [8,14], where b-endorphin was found to greatly increase in the blood during the perioperative period. The increment measured for each child across the three times was highly significant and showed a similar trend.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The study confirms the results reached in previous research in children [8,14], where b-endorphin was found to greatly increase in the blood during the perioperative period. The increment measured for each child across the three times was highly significant and showed a similar trend.…”
supporting
confidence: 92%
“…In general, drugs such as opioids [22] or benzodiazepines [36] strongly attenuate the b-endorphin response, whereas anaesthetics reduce it to a lesser degree [10,14,36]. The primary aim of this study was to confirm the increase of IR b-endorphin in the blood of children under perioperative conditions, as found in previous articles [2,8,14]. The secondary objective was to perform a systematic search for the factors which may influence the increment of this peptide during the perioperative period.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Cortisol is a glucocorticoid, secreted from cortex of suprarenal gland; its role in gluconeogenesis, metabolism of fat, CNS, muscle and renal function, vascular reactivity and the immune response has been studied extensively and is well known. It is also considered to be a surgical stress indicator [2]. The serum level increases in operated patients and directly correlates with the extent of surgical trauma [1].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in rats, ACTH returns to basal levels 24 hours after laparotomy, 18 and normalization of ACTH and cortisol values has been shown to occur within 24 hours in a prospective cohort of 78 children undergoing elective or emergency surgery. 19 Changes in ACTH have potential significance for the mechanism of action of RYBG. Recent studies indeed demonstrated abnormalities of the hypothalamic-pituitary-adrenal axis (HPA) in central obesity.…”
Section: The Role Of Adrenocorticotropic Hormonementioning
confidence: 99%